The Initial Stage of Pedagogic Research: Idea, Concept, Project - V. V. Sericov (Russian State Vocational Pedagogical University, 2015)
The paper deals with the main methodology ideas providing the basis for the pedagogic research projecting. The author describes what should be done to make the scientific research go ahead of the practical work and provide the new effec- tive ways of solving the educational problems, instead of presenting the well-known concepts. The author points out that one of the main aspects of methodology suggests a meaningful problem finding; the ways of implementing the research output into practice, interrelations with other sources of pedagogic knowledge, the mechanisms and possible ways of achieving the pedagogic goals being discussed. In conclusion, the project structure of a pedagogic research is given, wherein the essence of the project includes the concept, hypotheses and goals of the research. At the beginning, the project may seam rather abstract and subjective, however, as the research processes, these problems should be overcome. The special attention is given to the issue of the demand for pedagogic research and the conditions for its effective implementation in educational practice.